Application of Amberlite IRA-402 Modified by Means of 2-(-Sulphophenylazo)-1,8-dihydroxy-3,6-naphthalene Disulphonate for the Recovery of Cu(II), Co(II), Cd(II), Ni(II), Mn(II) and Fe(III) Ions - Monika Leszczyńska-Wawrzkiewicz; Zbigniew Hubicki (Adsorption Science & Technology)
2-( p -Sulphophenylazo)-1,8-dihydroxy-3,6-naphthalene disulphonate (SPADNS), an aromatic complexing agent, may be loaded onto the styrene–divinylbenzene matrix of a strongly basic anion-exchanger in order to obtain a chelating resin. The uptake of Cu(II), Co(II), Cd(II), Ni(II), Mn(II) and Fe(III) ions on Amberlite IRA-402 modified by SPADNS was studied at 25°C. Phase contact time, acid addition (HCl, H 2 SO 4 or CH 3 COOH) and temperature are the factors which determine SPADNS sorption when the batch technique is employed. The total and working ion-exchange capacities as well as the recovery factors for SPADNS were calculated.